WILLIAM WALLACE'S STRUGGLE FOR INDEPENDENCE: A CHARACTER ANALYSIS IN BRAVEHEART BY RANDAL WALLACE - Utama, Muhamad Mauda Putra; Ruminda, Ruminda; Faisal, Bunyamin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
This study examines the characteristics of William Wallace as the main character in leading Scotland to fight for its independence in the novel Braveheart by Randall Wallace, using Sudarmanto's theory of heroism. This study aims to identify the character depiction of the main character and analyze the character of William Wallace as the main character in the fight for Scottish independence in the novel Braveherat by Randall Wallace. The data used is to look at the dialogue and heroic actions of William Wallace as shown in the novel Braveheart by Randall Wallace. Research results: (1) To understand the meaning of the novel (2) Knowing William Wallace's characteristic struggle in fighting for Scotland's independence. (3) To understand the meaning of heroism. This study shows the character of the main character William Wallace in his struggle to liberate the Scottish people from British colonialism.